Experimental stand for studying the impact of laser-accelerated protons on biological objects. (April 2016) - Burdonov, K.F.; Eremeev, A.A.; Ignatova, N.I.; Osmanov, R.R.; Sladkov, A.D.; Soloviev, A.A.; Starodubtsev, M.V.; Ginzburg, V.N.; Kuzmin, A.A.; Maslennikova, A.V.; Revet, G.; Sergeev, A.M.; et al.
Abstract: An original experimental stand is presented, aimed at studying the impact of high-energy protons, produced by the laser-plasma interaction at a petawatt power level, on biological objects. In the course of pilot experiments with the energy of laser-accelerated protons up to, the possibility is demonstrated of transferring doses up to to the object of study in a single shot with the magnetic separation of protons from parasitic X-ray radiation and fast electrons. The technique of irradiating the cell culture HeLa Kyoto and measuring the fraction of survived cells is developed. The ways of optimising the parameters of proton beams and the suitable methods of their separation with respect to energy and transporting to the studied living objects are discussed. The construction of the stand is intended for the improvement of laser technologies for hadron therapy of malignant neoplasms.